Cost-effectiveness of cervical cancer screening and HPV vaccination: a Markov model from the healthcare payer perspective - Liu, Weixia; Jing, Li; Huang, Xiaojun; Huang, Hongxin; Jiang, Kuan Lie; Lu, Wei (Frontiers in Public Health, 2025)
BackgroundSubstantial progress has been made in cervical cancer screening and HPV vaccination in China. However, evidence on the cost-effectiveness of these interventions remains scarce, particularly for combined vaccination and screening strategies at the provincial level. To address this gap, we evaluated the cost-effectiveness of alternative cervical cancer prevention strategies in a southern province of China from the healthcare payer perspective.MethodsA Markov model was constructed to simulate a cohort of 100,000 females beginning at age 9 and followed until death (up to 100 years). The model compared the outcomes of bivalent, quadrivalent, and 9-valent HPV vaccines combined with two screening methods: TCT and HPV testing. Analyses were conducted from the healthcare payer perspective, considering only direct medical costs. The primary outcome was quality-adjusted life years (QALYs), discounted at 3% annually. Herd immunity effects were not incorporated. Model calibration relied on data from the China Health Statistics Yearbook, and sensitivity analyses assessed parameter uncertainty. Reporting followed the CHEERS 2024 guidelines.ResultsThirteen strategies were evaluated, including no intervention, screening alone, and combinations of screening with the three HPV vaccines. The combination of HPV testing and the 9-valent vaccine was the most cost-effective, with an incremental cost-effectiveness ratio (ICER) of ¥139.58 per QALY, well below the willingness-to-pay threshold. By contrast, TCT combined with the 9-valent vaccine yielded the highest ICER at ¥193,240.60 per QALY, exceeding the threshold. Sensitivity analyses showed ICER estimates were most influenced by screening coverage, vaccination uptake, test sensitivity, and the discount rate.ConclusionWithin the current resource and policy context, combining HPV testing with the 9-valent vaccine provides the highest economic value. This strategy offers evidence to guide future cervical cancer prevention policies in southern China.